Histological observations on lymphomyeloid organs of the Antarctic fish Trematomus bernacchii (Teleostei: Nototheniidae) - ROMANO N; BALDASSINI MR; TERRIBILI FR; MASTROLIA L; MAZZINI M.; ABELLI, Luigi (Polar Biology, 1997)
Lymphomyeloid organs of the Antarctic fish Trematomus bernacchii were studied with the aim of analysing some morphological aspects related to adap- tation to low environmental temperature. The thymus of T. bernacchii was flattened, incompletely lobated and scarcely regionalised. It was filled by lymphoid elements intermingled with stromal elements. The head kidney appeared highly vascularised and mainly lymphopoietic. The spleen appeared mainly erythropoietic, with scarcely developed areas of white pulp.